Dead cell and debris clearance in the atherosclerotic plaque: Mechanisms and therapeutic opportunities to promote inflammation resolution. (August 2021) - Dhawan, Umesh Kumar; Singhal, Aarushi; Subramanian, Manikandan
Abstract: Phagocytic clearance of dead cells and debris is critical for inflammation resolution and maintenance of tissue homeostasis. Consequently, defective clearance of dead cells and debris is associated with initiation and exacerbation of several autoimmune disorders and chronic inflammatory diseases such as atherosclerosis. The progressive loss of dead cell clearance capacity within the atherosclerotic plaque leads to accumulation of necrotic cells, chronic non-resolving inflammation, and expansion of the necrotic core, which triggers atherosclerotic plaque rupture and clinical manifestation of acute thrombotic cardiovascular adverse events. In this review, we describe the fundamental molecular and cellular mechanisms of dead cell clearance and how it goes awry in atherosclerosis. Finally, we highlight novel therapeutic strategies that enhance dead cell and debris clearance within the atherosclerotic plaque to promote inflammation resolution and atherosclerotic plaque stabilization. Graphical Abstract: ga1